Improving Health Outcomes and Serving Wider Society: The Potential Role of Understanding and Cultivating Prosocial Purpose Within Health Psychology Research and Practice to Address Climate Change and Social Isolation and Loneliness - Bains, Kiran Kaur; Turnbull, Triece (Frontiers in Psychology, 2019)
Human beings face unprecedented social and environmental challenges which require collective action and changes in health-related behavior. The threat of climate change is becoming an increasingly urgent issue for humanity and the natural environment. Alongside this, there is evidence that loneliness and social isolation can significantly impact cardiovascular health and mortality through direct and indirect processes, for example by increasing risky behaviors. However, one construct that has so far received little attention in health psychology is that of purpose. Purpose is thought to be self-regulatory; it derives from a greater sense of meaning yet is goal-directed and involves a stable and generalized intention toward accomplishment. The development of a sense of purpose is associated with improved mental and physical health. However, it is possible that one facet of purpose, prosocial orientation, may have a particularly beneficial effect on psychological well-being, increasing generativity and personal growth. Prosocial purpose may also help explain the growth in the number of people in the West who are reducing their meat and dairy intake, which may help mitigate climate change. It may also help explain the rise of civic engagement in environmental volunteering and support for conservation amongst some individuals and communities, which can also confer additional health benefits. Cultivating prosocial purpose may aid engagement in behavior change initiatives which may improve individual health and help address these wider social challenges, such as changing one’s diet to help address climate change, volunteering and engaging in physical activity outdoors to support the environment, and supporting active engagement with vulnerable groups at risk of social isolation and loneliness. Cultivating prosocial purpose may also support self-advocacy for social changes which can benefit community health. It may be possible to cultivate prosocial purpose through interventions which involve experiential and abstract learning experiences that increase empathy, stimulate reflection and lead to meaning-making processes. This may then facilitate development of a sense of prosocial purpose because meaning-making is thought to be a precursor to purpose development. Doing so may be important to engage populations in efforts to combat climate change and address social isolation and loneliness.